GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MEWUJUDKAN IKLIM ORGANISASI YANG KONDUSIF - Ali Ramatni; Nining Huriyati; Azwardi; Siminto; Al Ikhlas; Joni Wilson Sitopu (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Principal's transformational leadership style plays an important role in creating a conducive organizational climate in the school environment. This study aims to analyze the influence of the principal's transformational leadership style in building a positive work culture, increasing teacher motivation, and encouraging effective collaboration among all school stakeholders. The method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis. The results showed that principals who applied transformational leadership style were able to inspire a shared vision, provide individual motivation, and facilitate teachers' professional development. In addition, principals who act as transformational leaders can create a supportive work environment, increase team trust, and encourage innovation in the learning process. This study emphasizes the importance of implementing transformational leadership styles in an effort to improve the quality of school management and support the creation of a harmonious and productive organizational climate.